The routines of decision making - Betsch, Tilmann; Haberstroh, Susanne (Lawrence Erlbaum Associates, 2005)
Experience is currently a hot theme in decision making. For a long time, decision research was almost exclusively focused on new decisions and neglected the importance of experience. It took the field until the 1990s for a new direction in research and theorizing to become visible in the literature